Lobbyists - Croy, Anita (Inside American politics., 2019)
Describes the origins and history of lobbying in the American government, discusses who lobbyists are and what they do, and how lobbying works in Washington, D.C. today. Profiles the largest lobby groups, and discusses the dark side of lobbying. Includes color photographs, a glossary, and further resources.